2006
DOI: 10.1007/s00248-006-9130-0
|View full text |Cite
|
Sign up to set email alerts
|

Community Structure of the Bacteria Associated with Nodularia sp. (Cyanobacteria) Aggregates in the Baltic Sea

Abstract: The community structure of the bacteria associated with Nodularia spumigena (Mertens) cyanobacterial aggregates in the Baltic Sea was studied with temperature gradient gel electrophoresis (TGGE), using a 16S rRNA gene fragment as a target. Various developmental stages of the aggregates and free-floating cyanobacterial filaments were sampled to reveal possible changes in associated microbial community structure during development and senescence of the aggregates. The microbial community structures of all sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 54 publications
5
38
1
Order By: Relevance
“…Further, when we compared members of our library with common surface associated or algal associated organisms-for example, specific members of the Roseobacteria clade (Mayali et al, 2008;Wagner-Döbler et al, 2009) and 9% respectively of OTUs which share 97 PSI or better with their nearest GenBank relatives. These results are similar to those obtained during a study of the bacterial flora associated with another filamentous cyanobacterium, Nodularia, which found that the majority of epibiont clones associated with Nodularia represented novel taxa (Tuomainen et al, 2006). Our data suggest that the phycosphere associated with Trichodesmium and other cyanobacteria is a novel ecological niche host to unexplored genetic diversity.…”
Section: Puff and Tuft-type Trichodesmium Colonies Are A Unique Envirsupporting
confidence: 90%
See 2 more Smart Citations
“…Further, when we compared members of our library with common surface associated or algal associated organisms-for example, specific members of the Roseobacteria clade (Mayali et al, 2008;Wagner-Döbler et al, 2009) and 9% respectively of OTUs which share 97 PSI or better with their nearest GenBank relatives. These results are similar to those obtained during a study of the bacterial flora associated with another filamentous cyanobacterium, Nodularia, which found that the majority of epibiont clones associated with Nodularia represented novel taxa (Tuomainen et al, 2006). Our data suggest that the phycosphere associated with Trichodesmium and other cyanobacteria is a novel ecological niche host to unexplored genetic diversity.…”
Section: Puff and Tuft-type Trichodesmium Colonies Are A Unique Envirsupporting
confidence: 90%
“…These associations are the subject of numerous studies and in many cases have been found to be quite specific (Paerl & Gallucci, 1985;Fisher et al, 1998;Stevenson & Waterbury, 2006;Tuomainen et al, 2006) and in some cases, symbiotic . Bacteria colonize algae throughout their life-cycle and at all bloom stages and this colonization is not considered to be a sign of senescence or disease Sapp et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest NH 4 þ release was measured in colonies with the highest respiration relative to gross photosynthesis (Table 3). N. spumigena is usually colonized by a diverse community of bacteria exhibiting high ecto-enzymatic activities (Hoppe, 1981;Stoecker et al, 2005;Tuomainen et al, 2006), and a significant fraction of the primary production, measured by use of H 14 CO 3 in N. spumigena colonies from the Baltic Sea, was incorporated into the associated bacteria (Hoppe, 1981). Many pelagic bacteria are motile, show chemotaxis and their colonization rates of particles are in the order of minutes (Kiørboe et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in the Baltic Sea, Grossart et al (2003) found 100 to 360 times higher cell-specific protease and β-glucosidase activities, respectively, in aggregates compared to water surrounding the aggregates. As aggregates often harbor diverse communities of microorganisms that differ from their free living counterparts (DeLong et al, 1993;Bidle and Fletcher, 1995;Tuomainen et al, 2006), differences in microbial community structure may explain variations in the level of cell-specific activity.…”
Section: Introductionmentioning
confidence: 99%